2001
DOI: 10.1029/2000jc900148
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐shelf eddy heat transport in a wind‐free coastal ocean undergoing winter time cooling

Abstract: Abstract. A steady state cross-shelf density gradient of a wind-free coastal ocean undergoing winter time cooling is found for cooling and geometries which do not vary in the along-shelf direction. The steady state cross-shelf density gradient exists even when the average density of the water continues to increase. The steady state density gradient can be attained in less than a winter for parameters appropriate to the mid-Atlantic Bight. The cross-shelf eddy-driven buoyancy fluxes which cause this steady stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(101 citation statements)
references
References 31 publications
(20 reference statements)
7
92
2
Order By: Relevance
“…The prior modeling studies of coastal polynyas and simple open-shelf domains undergoing cooling have demonstrated a balance between surface buoyancy loss and cross-shelf eddy flux after an initial adjustment period [Chapman and Gawarkiewicz, 1997;Spall and Chapman, 1998;Pringle, 2001]. In some cases, the resultant density field achieves a steady state [Chapman and Gawarkiewicz, 1997;Spall and Chapman, 1998] with zero local change in average density, and in other cases, the crossshelf density gradient is constant in time [Pringle, 2001] with a small but nonzero remnant local change in density. However, all of these studies find that transports are dominated by eddy fluxes and transports in the surface and bottom boundary layers are insignificant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prior modeling studies of coastal polynyas and simple open-shelf domains undergoing cooling have demonstrated a balance between surface buoyancy loss and cross-shelf eddy flux after an initial adjustment period [Chapman and Gawarkiewicz, 1997;Spall and Chapman, 1998;Pringle, 2001]. In some cases, the resultant density field achieves a steady state [Chapman and Gawarkiewicz, 1997;Spall and Chapman, 1998] with zero local change in average density, and in other cases, the crossshelf density gradient is constant in time [Pringle, 2001] with a small but nonzero remnant local change in density. However, all of these studies find that transports are dominated by eddy fluxes and transports in the surface and bottom boundary layers are insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Prior modeling efforts [Gawarkiewicz and Chapman, 1995;Chapman and Gawarkiewicz, 1997;Spall and Chapman, 1998;Pringle, 2001] have shown crossshelf transports to play an important role in balancing the surface loss of heat, freshwater, and hence buoyancy. In this case, the cross-shelf and depth-averaged heat and salt balances can be written as…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations